2017
DOI: 10.1016/j.ic.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagonally non-computable functions and fireworks

Abstract: A set C of reals is said to be negligible if there is no probabilistic algorithm which generates a member of C with positive probability. Various classes have been proven to be negligible, for example the Turing upper-cone of a non-computable real, the class of coherent completions of Peano Arithmetic or the class of reals of minimal Turing degree. One class of particular interest in the study of negligibility is the class of diagonally noncomputable (DNC) functions, proven by Kučera to be non-negligible in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Dorais, Hirst, and Shafer [5], building on the aforementioned work of Ambos-Spies, et al [1], have shown that the reverse mathematics principle "there exists a k such that for every function f there is a k-bounded function that is DNC relative f " does not imply the existence of a {0, 1}-valued DNC function in the absence of Σ 0 2 induction, answering a question of Simpson. Bienvenu and Patey [3], by combining bushy tree arguments with probabilistic ones, have shown that there is a computable function h such that every 2-random real computes an h-bounded DNC function that computes no Martin-Löf random real.…”
Section: Introductionmentioning
confidence: 99%
“…Dorais, Hirst, and Shafer [5], building on the aforementioned work of Ambos-Spies, et al [1], have shown that the reverse mathematics principle "there exists a k such that for every function f there is a k-bounded function that is DNC relative f " does not imply the existence of a {0, 1}-valued DNC function in the absence of Σ 0 2 induction, answering a question of Simpson. Bienvenu and Patey [3], by combining bushy tree arguments with probabilistic ones, have shown that there is a computable function h such that every 2-random real computes an h-bounded DNC function that computes no Martin-Löf random real.…”
Section: Introductionmentioning
confidence: 99%
“…We prove that the jump of A − (X) can be described with the cluster point representation. This enables us to prove in Section 4 that (for perfect Polish spaces) 3 . In other words, the change of the input space from A − (X) to A + (X) can equivalently be expressed by an application of the jump.…”
mentioning
confidence: 89%
“…On the other hand, BCT 0 and BCT 2 are both ω-indiscriminative and hence also indiscriminative: since BCT 0 and BCT 2 are each densely realized, 3 by the Baire Category Theorem (1.2) itself, this follows from [14,Proposition 4.3]. Moreover, 3 A notion introduced in [14], which roughly speaking, says that the image of BCT 0 and BCT 2 is densely covered over all realizers. every jump of BCT 0 or BCT 2 is also ω-indiscriminative, since it is merely a property of the image.…”
Section: Parallelizabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A more intuitive proof can be given using a fireworks argument (which takes its name from the presentation by Rumyantsev and Shen [RS14] with an analogy about purchasing fireworks from a purportedly corrupt fireworks salesman), an approach that is more suitable for our purposes. The mechanics of fireworks arguments are already thoroughly explained in [RS14] and [BP17], but we shall review them for the sake of completeness.…”
Section: Firework Argumentsmentioning
confidence: 99%